Overexpression of claspin promotes docetaxel resistance and is associated with prostate‐specific antigen recurrence in prostate cancer. (9th July 2021) - Babasaki, Takashi; Sentani, Kazuhiro; Sekino, Yohei; Kobayashi, Go; Thang Pham, Quoc; Katsuya, Narutaka; Akabane, Shintaro; Taniyama, Daiki; Hayashi, Tetsutaro; Shiota, Masaki; Oue, Naohide; Teishima, Jun; et al.
Abstract: Although docetaxel (DTX) confers significant survival benefits in patients with castration‐resistant prostate cancer (CRPC), resistance to DTX inevitably occurs. Therefore, clarifying the mechanisms of DTX resistance may improve survival in patients with CRPC. Claspin plays a pivotal role in DNA replication stress and damage responses and is an essential regulator for the S‐phase checkpoint. CLSPN is an oncogenic gene that contributes to tumor proliferation in several human solid tumors. However, the clinical significance of claspin in prostate cancer (PCa) has not been examined. The present study aimed to elucidate the role of claspin and its relationship with DTX resistance in PCa. We immunohistochemically analyzed the expression of claspin in 89 PCa cases, of which 31 (35%) were positive for claspin. Claspin‐positive cases were associated with higher Gleason score, venous invasion, and perineural invasion. Kaplan–Meier analysis showed that high claspin expression was related to poor prostate‐specific antigen (PSA) relapse‐free prognosis. In a public database, high CLSPN expression was associated with poor PSA relapse‐free prognosis, Gleason score, T stage, lymph node metastasis, CRPC, and metastatic PCa. Claspin knockdown by siRNA decreased cell proliferation, upregulated DTX sensitivity, and suppressed the expression of Akt, Erk1/2, and CHK1 phosphorylation in DU145 and PC3 cell lines. Furthermore, claspin expression was much more upregulated in DTX‐resistant DU145 (DU145‐DR) than in parental DU145 cells. Claspin knockdown significantly upregulated the sensitivity to DTX in DU145‐DR cells. These results suggest that claspin plays an important role in PCa tumor progression and DTX resistance. Abstract : Claspin overexpression was related to poor PSA relapse‐free prognosis. Claspin knockdown significantly upregulated the sensitivity to docetaxel in DU145 docetaxel‐resistant cells.